Upper Airway Resistance Measurement with Esophageal Catheter and Oscillometry - Chavoshian, Shaghayegh; Montazeri Ghahjaverestan, Nasim; Cao, Xiaoshu; Stanbrook, Matthew B; Tarlo, Susan M; Yadollahi, Azadeh (CMBES Proceedings, 2024)
Esophageal catheters equipped with multiple sensors are typically inserted nasally to reach the esophagus, to measure a range of pressure. These measurements can detect variations in pressure caused by obstructions at different points in the respiratory tract. Pressure sensors along the catheter are positioned differently based on the different anatomical structures of the respiratory tract among individuals. Our research is thus focused on investigating the association between pharyngeal airway resistance obtained from different pressure sensors with the gold standard measurement. We calculated the pressure difference of two sensors relative to atmosphere pressure and estimated pharyngeal airway resistance at the corresponding locations using multiple linear regression models on pressure, airflow, and volume. The gold standard measurement to assess pharyngeal airway resistance was Oscillometry. Participants were grouped by sex, height, and age, and the association of resistance between the two approaches was examined using the Bland-Altman plot and Pearson correlation. In our study, 19 adult participants were included. Our data suggested that those who are either male, taller, or older adults have a longer pharyngeal length compared to female, short, or middle-aged adults. Therefore, to assess pharyngeal airway resistance using a catheter for these groups, we should opt for more proximal pressure sensors, as the distal sensor is placed deeper into the esophagus. This can have significant implications for research studies analyzing data from esophageal catheters.